Konsep Penanaman dan Pertumbuhan Gereja: Menabur dengan Cerdik dan Menuai dengan Tulus - Halawa, Ririn Valentina (Institut Agama Kristen Negeri Tarutung, 2023)
A church does not exist in an empty space, but it exists in the midst of a multi-problematic world and environment. In general, the church is known by Christians who are centered on the figure of Jesus Christ. However, the problem of the church is that it does not experience growth in the church and worship. The purpose of writing this article is to provide strategies for planting and growing the Church with the principle of sowing cleverly and reaping sincerely. The writing of this article utilizes the literature method, which uses books, journal articles and Bible texts as references in solving the concept of church planting and growth. The result of the research of this article states that the church will experience growth, if the leaders and congregation can work together to improve the spiritual experience.